Answer:
Step-by-step explanation:
sin ∠R = SQ/SR
<u>This is same as:</u>
Correct option is b)
Answer:
1/x+5
Step-by-step explanation:
1. Rewrite 3x as a difference
x-2/x^2 + 5x-2 - 10
2. Factor out x from the equation, then factor out -2.
x-2/ x+(x+5) - 2(x+5)
3. Factor out x+5 from the expression
x-2/ (x+5)(x-2)
4. Reduce the fraction with x-2
x-2 / (x+5) x-2
1/x+5
Answer:
x = 5
Step-by-step explanation:
The difference between consecutive terms will be equal , then
a₂ - a₁ = a₃ - a₂ , that is
x + 9 - (3x - 2) = 2x + 5 - (x + 9) ← distribute parenthesis on both sides
x + 9 - 3x + 2 = 2x + 5 - x - 9 , simplify both sides
- 2x + 11 = x - 4 ( subtract x from both sides )
- 3x + 11 = - 4 ( subtract 11 from both sides )
- 3x = - 15 ( divide both sides by - 3 )
x = 5
<u>Answer</u>
C. 39.71
<u>Explanation</u>
33 = p - 6.71
The first step is to make the like terms to be on the same side.
Add 6.71 on both sides of the eqution
33 + 6.71 = p - 6.71 + 6.71
39.71 = p
∴ p = 39.71
Answer: x ≥ 0
Step-by-step explanation:
First, let's define the symbols used:
a < x (this means that a is strictly smaller than x)
a > x (this means that a is strictly larger than x)
a ≤ x (this means that a is smaller than or equal to x)
a ≥ x (this means that a is larger than or equal to x)
Now we have the statement "x is no less than 0"
Then x can be equal to zero, or larger than zero, but never smaller than zero.
Looking at the symbols above, we know that we need to use:
x ≥ 0
(this is equivalent to the statement)